Numerical modelling of the variability of the vibration frequencies of multi-layered timber structures using the modal stability procedure. (1st April 2022) - Bui, T.A.; Lardeur, P.; Oudjene, M.; Park, J.
Abstract: Based on the Modal Stability Procedure (MSP), this paper investigates numerical variability of vibration frequencies of novel adhesive free engineered wood products (AFEWPs), namely adhesive free laminated timber beams (AFLB) and adhesive free cross-laminated timber panels (AFCLT), assembled through thermo-mechanically compressed wood dowels. Structures are modelled by finite element method with twenty-node hexahedral solid elements. Several new variants of MSP formulation for the twenty-node solid element have been developed, and the most suitable one using an efficient diagonal mass matrix was selected for the study. Statistical characteristics of the frequencies obtained from the MSP formulation are compared with those obtained from a direct Monte Carlo Simulation. Comparison of computational cost between the MSP formulation and the direct Monte Carlo Simulation is also presented, showing the efficiency of the MSP formulation.